Successful Social Media and Ecommerce Strategies in the Wine Industry - Sznolnoki, Gergely; Thach, Liz; Kolb, Dani (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Social media and ecommerce has an enormous impact in today's wine industry, particularly among the Internet-savvy millennial generation. This book analyzes new communication platforms used in digital wine marketing, allowing students and researchers to understand how both producers and consumers deal with these modern communication and selling platforms. Providing in-depth examples from around the world, the contributing authors explore how wineries use Facebook and other social media platforms to interact with consumers, crowdsourcing techniques to build a new wine business, cross-cultural analysis, and other tactics that give insight into the world of digital wine marketing.